ETUDE DU COMPORTEMENT DES CONSOMMATEURS DES PRODUITS TABACICOLES FACE AUX NOTICES DES PREVENTIONS SANITAIRES - Mendo, Germain Elembo; Mokili, Mobondo; Mendo, Fabrice Wembo (IJRDO - Journal of Social Science and Humanities Research, 2023)
Our study focuses on how consumers of tobacco products observe health prevention notices.For information, it was around the 1990s that the WHO or the World Health Organization, had introduced a request to the United Nations headquarters, saying that 80% of smokers die from tobacco. To protect the world’s population, the WHO is ready to pay the lost profits for the companies that manufacture the world’s Tobacco products and that these companies transform their factories into manufacturers of other products.To give their opinions, his companies have asked the WHO to go to his bosses who are the end consumers to collect the data that will allow the two parties to make a final decision. After two years of survey of smokers in the 5 continents and the results were 78.64% against the closure of tobacco manufacturing plants.Given the results of the survey, and especially that the largest companies were in developed countries where democracy is respected, a commission of WHO experts and companies that represented the Tobacco side.The two parties have agreed to put smokers before their own responsibility ; that is to say, put health prevention notices on cigarette packets and components.